1989
DOI: 10.1159/000185325
|View full text |Cite
|
Sign up to set email alerts
|

Studies of a Glomerular Permeability Factor in Patients with Minimal-Change Nephrotic Syndrome

Abstract: Peripheral blood mononuclear cells (PBMC) from patients with minimal-change nephrotic syndrome (MCNS) were tested for their ability to produce a factor which increases the urinary protein excretion levels of rats. It was shown that enhanced proteinuria can be produced in 8-hour urine specimens from rats by the injection of concentrated supernatants of cultured concanavalin-A-stimulated PBMC of patients with MCNS, but not from other nephrotics or normal subjects. The increase in urinary protein excretion was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 15 publications
0
45
0
Order By: Relevance
“…Data from the literature suggest that cells that are responsible for MCNS are from the immune system, more specifically from the T cell subset. A possible role for T cells developed from the observation that infusion of supernatants of cultured PBMC from patients with MCNS relapses induced proteinuria in rats [25][26][27][28] and that T cell hybridomas obtained from a patient with NS secreted a factor that caused proteinuria in rats. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Data from the literature suggest that cells that are responsible for MCNS are from the immune system, more specifically from the T cell subset. A possible role for T cells developed from the observation that infusion of supernatants of cultured PBMC from patients with MCNS relapses induced proteinuria in rats [25][26][27][28] and that T cell hybridomas obtained from a patient with NS secreted a factor that caused proteinuria in rats. 29 …”
Section: Discussionmentioning
confidence: 99%
“…No studies, however, have yet demonstrated that phenotypic changes correspond to functional changes of PBL in various nephrotic stages. As to the approach with functional changes, several investigators have suggested that the alteration in peripheral blood T cell function results in the release of a certain cytokine which decreases the glomerular polyanions leading to proteinuria [5, 6, 14]. On the other hand, some previous studies by flow cytometry have been performed to detect the phenotypic changes, however, there have been no consistent results [3, 15, 16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…It was further postulated that a certain cytokine/vascular permeability factor secreted by concanavalin-A-stimulated lymphocytes in INS patients can induce proteinuria [5, 6]. However, it has not been clarified which subpopulations of PBL and which cytokine play a major role in those lymphocyte dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, immediate recurrences after transplantation have been successfully treated by plasma exchanges or plasma immunoadsorption techniques [20][21][22]. An-other line of evidence suggesting secretion of a permeability factor comes from experiments showing that systemic infusion of supernatants of cultured PBMC or T cells of patients with MCNS relapse induces proteinuria in rats [23][24][25][26][27]. Immunochemical analyses of affinity column eluate fractions that induced proteinuria suggested that the molecular weight of the permeability factor is below 150 kDa.…”
Section: Research On Permeability Factormentioning
confidence: 99%